Byrsonima (Malpighiaceae) from Espírito Santo state, Brazil - Alves, Livia Lara; Francener, Augusto; Costa, Maria Tereza R.; Sobral, Marcos (Phytotaxa, 2021)
We present a floristic survey for Byrsonima (Malpighiaceae) from Espírito Santo state, Brazil. Of the 17 species occurring in Espírito Santo, one is recorded for the first time for the state (B. intermedia). In addition, three species were considered vulnerable or near threatened (B. alvimii, B. bahiana and B. cacaophila). Identification key for all species was presented, along with morphological descriptions, photograph plates, distribution maps, and ecological notes of the studied species.